Merging Community Planning and Organizing: The Erosion of Urban Rights and New Alliances in New Orleans’s Lower 9th Ward - Antonio Raciti; Kenneth M. Reardon (lo Squaderno)
Using the case of Post-Hurricane Katrina New Orleans (Louisiana, USA), this essay argues for an Empowerment Planning (EP) approach to planning practice that integrates Community Planning (CP) with Community Organizing (CO) to address growing conditions of inequality and vulnerability in urban settings. The article explores the case of planning in New Orleans Lower 9th Ward following the City’s devastation caused by Hurricane Katrina in 2005. It focuses on the cultural framework within which CP and CO have developed and eventually shaped the EP approach. EP has grown precisely due to the limits of CP in the absence of CO and vice versa and, therefore, from having created a practice that builds upon the combined strengths of these two approaches. It facilitates the implementation of winning practices in situations where the erosion of fundamental spatial rights has been a longstand- ing concern. In the wake of Katrina, New Orleans experienced a massive erosion of urban rights, including housing and access to basic public services. This condition prompted a social uprising that led to the birth of new alliances between residents, community organizations, and academic institutions that used EP to explore the nexus between contingent urban precarity and new urban partnerships.